2022
DOI: 10.3389/ffunb.2022.1002161
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma – genomes and genomics as treasure troves for research towards biology, biotechnology and agriculture

Abstract: The genus Trichoderma is among the best studied groups of filamentous fungi, largely because of its high relevance in applications from agriculture to enzyme biosynthesis to biofuel production. However, the physiological competences of these fungi, that led to these beneficial applications are intriguing also from a scientific and ecological point of view. This review therefore summarizes recent developments in studies of fungal genomes, updates on previously started genome annotation efforts and novel discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 264 publications
0
13
0
Order By: Relevance
“…One striking example of horizontal gene transfer (HGT) was described for the sorbicillin biosynthetic cluster in T. reesei, which was acquired from other fungi, but also other cases are known from this genus (Druzhinina et al, 2018;Druzhinina et al, 2016;Schalamun & Schmoll, 2022). An unexpectedly high .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One striking example of horizontal gene transfer (HGT) was described for the sorbicillin biosynthetic cluster in T. reesei, which was acquired from other fungi, but also other cases are known from this genus (Druzhinina et al, 2018;Druzhinina et al, 2016;Schalamun & Schmoll, 2022). An unexpectedly high .…”
Section: Discussionmentioning
confidence: 99%
“…Fungi of the genus Trichoderma (Schalamun & Schmoll, 2022;Woo et al, 2022) are typical inhabitants of the rhizosphere and are found in soils worldwide (Druzhinina et al, 2011). They belong to the most versatile microorganisms for both agricultural and industrial applications (Mukherjee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gene families such as ankyrin, heterokaryon incompatibility domain protein (HET), TF, carbohydrate degradative, and secondary metabolism genes all present high polymorphism rates (Kubicek et al, 2011, 2019; Mukherjee et al, 2013). The intraspecific diversity of the Harzianum clade poses a challenge to even modern molecular genetics because this species aggregate has multiple infra groups and great complexity (Druzhinina et al, 2010; Kubicek et al, 2019; Schalamun and Schmoll, 2022), which can partially explain the limited CAZyme transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Their remarkable capacities at the intraspecific level are greatly influenced by lateral gene transfer and other complex evolutionary processes contributing to genomic variations, even those observed in closely related species. Interestingly, carbohydrate metabolism and biocontrol gene families seem to be especially influenced by evolutionary processes (Kubicek et al, 2011; Kubicek et al, 2019; Hewedy et al, 2020; Sood et al, 2020; Schalamun and Schmoll, 2022; Tyśkiewicz et al, 2022; Guzmán-Guzmán et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Trichoderma comprises a diverse array of mostly bene cal fungi, which comprise plant symbionts and industrial workhorses for enzyme production [35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%